Draft Genome Sequence of Pseudomonas sp. Strain In5 Isolated from a Greenlandic Disease Suppressive Soil with Potent Antimicrobial Activity - Hennessy, Rosanna C. (Genome Announc, 2015)
Pseudomonas sp. In5 is an isolate of disease suppressive soil with potent activity against pathogens. Its antifungal activity has been linked to a gene cluster encoding nonribosomal peptide synthetases producing the peptides nunamycin and nunapeptin. The genome sequence will provide insight into the genetics behind the antimicrobial activity of this strain.